The relationship between shareholders and shubuhat: A study on the Islamic banks in Malaysia - Essia Ries, Ahmed; Md. Aminul Islam, Prof. Madya Dr.; Fatma Nasser, Al-Harthy (Asian Economic and Social Society, 2013)
Link to publisher's homepage at http://www.aessweb.com/